1995
DOI: 10.1080/09553009514550141
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic Growth Factors in the Treatment of Therapeutic and Accidental Irradiation-induced Bone Marrow Aplasia

Abstract: Bone marrow aplasia is one of the main syndromes following a high dose accidental exposure of ionizing radiation. Although both transfusion and bone marrow transplantation have been used with some success since the first treatments of patients, other therapeutic strategies are needed. The strategies involving haematopoietic growth factors for the treatment of radiation victims have been explored in vivo mainly in animal models and it is hoped that new therapeutic regimens will be elucidated from such approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 65 publications
0
18
0
3
Order By: Relevance
“…7,26 In most preclinical trials, HGF administration starts from the day after myeloablative injury, and the duration of treatment covers 15 to 21 days until neutrophil or platelet recovery. [2][3][4][5][6]27 Few combinations have been used despite promising studies in myeloablated nonhuman primates that entailed 2 cytokines 4-6 or synthetic dual cytokine receptor agonists. 3,27 Thus far, nuclear accident victims have been treated with GM-CSF and IL-3 28 or G-CSF ϩ GM-CSF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,26 In most preclinical trials, HGF administration starts from the day after myeloablative injury, and the duration of treatment covers 15 to 21 days until neutrophil or platelet recovery. [2][3][4][5][6]27 Few combinations have been used despite promising studies in myeloablated nonhuman primates that entailed 2 cytokines 4-6 or synthetic dual cytokine receptor agonists. 3,27 Thus far, nuclear accident victims have been treated with GM-CSF and IL-3 28 or G-CSF ϩ GM-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…1 Numerous studies have shown the efficacy of hematopoietic growth factors (HGFs) in stimulating neutrophil and platelet recovery in animals and humans after myeloablation. 2 Granulocyte-colony-stimulating factor (G-CSF), granulocyte macrophage-colony-stimulating factor (GM-CSF), interleukin-3 (IL-3), IL-11, and thrombopoietin (TPO) are among the most efficient cytokines. 3 These molecules have primarily been evaluated as monotherapy, but the simultaneous or sequential administration of 2 complementary cytokines has resulted in better patterns of hematologic recovery.…”
Section: Introductionmentioning
confidence: 99%
“…1 The rationale of HGF treatment is the presence of residual hematopoietic stem and progenitor cells (HSPCs) in BM areas after total body irradiation (TBI) due to the constitutive heterogeneity of dose distribution involving notably the attenuation related to body thickness. 2,3 These "underexposed" HSPCs represent useful targets in order to accelerate hematopoietic recovery in addition to intrinsic radio-resistant stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Cette difficulté est essentiellement due au manque de bio-indicateurs de l'étendue des dommages radio-induits et en particulier des dommages au système hématopoïétique. En effet, le choix entre différents traitements du syndrome hématopoïétique, c'est-à-dire thérapie de soutien, injection de cytokines (Butturini et al, 1988 ; Mac Vittie et Monroy, 1990 ; Thierry et al, 1995) ou greffe de moelle osseuse (Mathé et al, 1964 ;Baranov et al, 1989 ;Gale et Butturini, 1991), est surtout basé sur l'estimation de la dose reçue par la victime plutôt que sur l'étendue des dommages radio-induits à la moelle osseuse (Gale, 1988). Cependant, l'étude des accidents d'irradiation passés montre clairement que dans la plupart des cas, l'irradiation est hétérogène (Bond et al, 1953 ;Nénot, 1998).…”
Section: La Nécessité Des Bio-indicateurs D'effet De L'irradiationunclassified